Pengaruh Aromaterapi Lemon (Citrus) terhadap Skala Nyeri Dismenorea pada Mahasiswi Program Studi Ilmu Keperawatan STIKes Baiturrahim Jambi - Vita Febriyanti; Vevi Suryenti Putri; Rahmi Dwi Yanti (Jurnal Akademika Baiturrahim Jambi, 2021)
Dysmenorrhea is a complaint that is often experienced by women during menstruation. Pain management can be done with complementary measures, one of which is by giving lemon aromatherapy (citrus). Lemon aromatherapy contains limonene which can inhibit prostaglandins thereby reducing pain. The purpose of this study was to determine the influence of Lemon Aromatherapy (Citrus) on dysmenorrhea pain scales at students nurse study program the college health science BaiturrahimJambi.This study was conducted by pre-experimental method with a one- group-pre-test-post-test design conducted at the respondent's home. The respondents were 20 females students who experienced dysmenorrhea. This study was conducted on June - July 2020. This study its mean before administration was 4.45 and after administration the mean was 3.25. Based on the results of statistical analysis using the Paired t test, the p-value was 0,000 (p<0.05).It can be concluded that there is an influence of  lemon aromatherapy (citrus) on dysmenorrhea pain scales at students nurse study program the college health science Baiturrahim Jambi